Gross Morphological Studies on the Moderator Bands of Different Domestic Animals - Hareeswaraiah, M. (Indian Journal of Veterinary Anatomy, 2020)
In buffalo and pig heart, the right ventricle showed single unbranched moderator band and it was extended from middle of interventricular septum to the lower part of the anterior papillary muscle. Similarly, in heart of sheep and goat often one and rarely two moderator bands were present. In dog, the right ventricle showed more than one moderator band with variation on their termination. The average length of moderator band in right ventricle was larger in buffalo followed by sheep, goat and pig. In buffaloes, the left ventricle moderator band was single and highly branched and formed a network like arrangement. In sheep, goat, pig and dog the left ventricle showed more than one moderator band of different sizes, they were categorized into small, medium and large sized and these were unbranched but some showed two or three attachments with the ventricular wall.